Supreme Committee for the Liberation of Lithuania (VLIK) 1986–1992: the Mission of Liberation Accomplished - Banionis , Juozas (Genocidas ir rezistencija, 2015)
In the second half of the 1980s, the Supreme Committee for the Liberation of Lithuania (VLIK), which aimed at “restoration of the enforcement of the sovereign rights of Lithuania”, called on other Lithuanian emigrant political organisations, together with emigrants from all Baltic countries, to organise a broader campaign to this end during the meeting of the European Conference on Security and Cooperation (CSCE) in Vienna (for example, in 1986 Lithuanians, together with emigrants from all Baltic countries, took part in a joint demonstration in Vienna).